How Streptomyces anulatus Primes Grapevine Defenses to Cope with Gray Mold: A Study of the Early Responses of Cell Suspensions - Vatsa-Portugal, Parul; Aziz, Aziz; Rondeau, Marine; Villaume, Sandra; Morjani, Hamid; Clément, Christophe; Ait Barka, Essaid (Frontiers in Plant Science, 2017)
Gray mold, caused by Botrytis cinerea, is one of the most destructive diseases of grapevine and is controlled with an intense application of fungicides. As alternatives to chemicals, beneficial microbes may promote plant health by stimulating the plant's immune system. An actinomycete, Streptomyces anulatus S37, has been screened from the rhizosphere microbiome of healthy Vitis vinifera on the basis of its ability to promote grapevine growth and to induce resistance against various phytopathogens, including B. cinerea. However, molecular mechanisms involved locally after direct perception of these bacteria by plant cells still remain unknown. This study focuses on local defense events induced in grapevine cells during interactions with S. anulatus S37 before and after pathogen challenge. We demonstrated that S. anulatus S37 induced early responses including oxidative burst, extracellular alkalinization, activation of protein kinases, induction of defense gene expression and phytoalexin accumulation, but not the programmed cell death. Interestingly, upon challenge with the B. cinerea, the S. anulatus S37 primed grapevine cells for enhanced defense reactions with a decline in cell death. In the presence of the EGTA, a calcium channel inhibitor, the induced oxidative burst, and the protein kinase activity were inhibited, but not the extracellular alkalinization, suggesting that Ca2+ may also contribute upstream to the induced defenses. Moreover, desensitization assays using extracellular pH showed that once increased by S. anulatus S37, cells became refractory to further stimulation by B. cinerea, suggesting that grapevine cells perceive distinctly beneficial and pathogenic microbes.